Technologies to Study Action Potential Propagation With a Focus on HD-MEAs - Emmenegger, Vishalini; Obien, Marie Engelene J.; Franke, Felix; Hierlemann, Andreas (Frontiers in Cellular Neuroscience, 2019)
Axons convey information in neuronal circuits via reliable conduction of action potentials from the axon initial segment to the presynaptic terminals. Recent experimental findings increasingly evidence that the axonal function is not limited to the simple transmission of action potentials. Advances in subcellular-resolution recording techniques have shown that axons display activity-dependent modulation in spike shape and conduction velocity, which influence synaptic strength and latency. We briefly review, here, how recent methodological developments facilitate the understanding of the axon physiology. We included the three most common methods, i.e. genetically encoded voltage imaging, subcellular patch-clamp and high-density microelectrode arrays (HD-MEAs). We then describe the potential of using HD-MEAs in studying axonal physiology in more detail. Due to their robustness, amenability to high-throughput and high spatiotemporal resolution, HD-MEAs can provide a direct functional electrical readout of single cells and cellular ensembles at subcellular resolution. HD-MEAs can, therefore, be employed in investigating axonal pathologies, the effects of large-scale genomic interventions (e.g., with RNAi or CRISPR) or in compound screenings. A combination of extracellular microelectrode arrays, intracellular microelectrodes and optical imaging may potentially reveal yet unexplored repertoires of axonal functions.